Toward same-day detection of Salmonella: a rapid and cost-effective analytical method - Cristiano, Daniela; Peruzy, Maria Francesca; Castellano, Silvia; Mancusi, Andrea; Proroga, Yolande Thérèse Rose; Delibato, Elisabetta; Mazzocca, Roberta; Ambrosio, Rosa Luisa; Murru, Nicoletta (Frontiers in Microbiology, 2025)
IntroductionConventional methods for Salmonella detection in food samples are time-consuming, often requiring up to 5 days for pathogen identification. To prevent the distribution of contaminated foods on the market, rapid methods for early Salmonella detection are urgently needed, especially within the food industry, where timely responses are critical to public health and supply chain management. The aim of the present study was to evaluate a rapid strategy based on Real-Time PCR for detecting Salmonella in various food matrices.MethodsSeveral approaches were tested to rapidly detect Salmonella in experimentally contaminated leafy greens, minced meat, mozzarella cheese, and mussel samples. The protocols included two DNA extraction methods (boiling and Chelex 100), two enrichment broths (BPW and BPW supplemented with RAPID’Salmonella Capsules), and two incubation temperatures (37 °C and 42 °C).ResultsUsing preheated BPW at 41.5 °C overnight, Salmonella was detectable within 4 h when DNA was extracted via the Chelex 100 method.DiscussionThe application of this rapid, automated, and low-cost analytical strategy could enable both food business operators and competent authorities to significantly enhance the control of food products. This method may represent an innovative tool for improving the assessment of epidemic outbreaks, ensuring not only food safety but also rapid diagnosis during emergencies.